Efforts to Improve the Performance of Dialogical Patrol of Turjawali Sat Samapta Unit in the Prevention of Motor Vehicle Theft Crime in the Jurisdiction of the Mojokerto Police District - Simatupang, Ferditho Alehandro (Police Studies Review, 2024)
In welcoming the golden Indonesia 2045, in accordance with the fourth paragraph of the preamble to the 1945 Constitution, security must be maintained through the maintenance of public security and order. The National Police carries out efforts to maintain public security and order through police actions tailored to public security and order disturbances. Motor vehicle theft is one example of public security and order disorders in the Mojokerto Regency area experiencing an increase in cases. This study focuses on Sabhara as the backbone of the National Police in carrying out preventive actions, namely dialogical patrols to prevent criminal acts of motor vehicle theft by knowing the implementation of dialogical patrols, influencing factors, and performance improvement efforts carried out by the Turjawali Sat Samapta unit of the Mojokerto Police District. This research uses literature in the form of POAC management theory, Laswell communication theory, 6M theory which is focused on 4 M, and SWOT which is also associated with several concepts such as effort, performance, crime prevention concept, dialogical patrol concept, and curanmor concept. This type of research is qualitative research with field research methods that use data collection techniques which are then analyzed and conclusions drawn. The implementation of patrols is generally guided by Perkabaharkam No 1 of 2017, but the results of the study found that the Turjawali Sat Samapta unit of the Mojokerto Police District is still not fully guided by this. The implementation of the dialogue method in dialogical patrols is also still not on target and has a significant impact on the community. The obstacles that exist are more influential than those that support the implementation of patrols. Performance improvement efforts carried out have also not been able to touch the root of the existing problem. Special attention is needed, especially involving technology to improve the quality of the implementation of dialogical patrols of the Turjawali Sat Samapta Unit of the Mojokerto Police District in preventing curanmor from having a significant impact on the community.